Conmemoración del sesquicentenario del Código Civil de Andrés Bello: un análisis de las razones de su celebridad - Tapia R., Mauricio (Revista Chilena de Historia del Derecho, 2008)
The author dedicates his work to explain the reasons that gave frame to the Civil Code of Chile, which can be grouped in two: the essential contents of this text and its value as a symbol. On the first aspect, he emphasizes, that this code achieved an admirable transaction between tradition and innovation; therefore, though it conserves many aspect of the hispanic-indian law, it also receives influence of the French Revolution, such as the importance given to liberty, equiality and will. The Code, besides, tried to continue a rationalistic natural order generalizing rules oriented in the medieval Ius Commune. As for value of the Code as a symbol, the author attributes it to the personality of Andrés Bello, to the longevity of the text and to the international diffusion that it achieved.